Possibilities and challenges for developing a successful vaccine for leishmaniasis. Issue 1 (December 2016) - Srivastava, Saumya; Shankar, Prem; Mishra, Jyotsna; Singh, Sarman
Abstract Leishmaniasis is a vector-borne disease caused by different species of protozoan parasites of the genusLeishmania . It is a major health problem yet neglected tropical diseases, with approximately 350 million people worldwide at risk and more than 1.5 million infections occurring each year. Leishmaniasis has different clinical manifestations, including visceral (VL or kala-azar), cutaneous (CL), mucocutaneous (MCL), diffuse cutaneous (DCL) and post kala-azar dermal leishmaniasis (PKDL). Currently, the only mean to treat and control leishmaniasis is by rational medications and vector control. However, the number of available drugs is limited and even these are either exorbitantly priced, have toxic side effects or prove ineffective due to the emergence of resistant strains. On the other hand, the vector control methods are not so efficient. Therefore, there is an urgent need for developing a safe, effective, and affordable vaccine for the prevention of leishmaniasis. Although in recent years a large body of researchers has concentrated their efforts on this issue, yet only three vaccine candidates have gone for clinical trial, until date. These are: (i) killed vaccine in Brazil for human immunotherapy; (ii) live attenuated vaccine for humans in Uzbekistan; and (iii) second-generation vaccine for dog prophylaxis in Brazil. Nevertheless, there are at least half a dozen vaccine candidates in the pipeline. One can expect that, in the near future, the understanding of the whole genome ofLeishmania spp. will expand the vaccine discovery and strategies that may provide novel vaccines. The present review focuses on the development and the status of various vaccines and potential vaccine candidates against leishmaniasis.